To applicability of surgical correction for brachymetatarsia in children - Oleg V. Kozhevnikov; Aleksandr A. Ochkurenko; Aleksey V. Ivanov; Inna V. Gribova; Svetlana E. Kralina; Yulia V. Gavrilova (Гений oртопедии, 2020)
Introduction Correction of brachymetatarsia is performed by lengthening with various means. The necessity of metatarsal bone lengthening in brachymetatarsia is debatable. Material and methods From 2004 to 2018, surgical correction of brachymetatarsia was performed in 13 patients (age range, 6–18 years). Biomechanics of walking was studied in the preoperative and long-term postoperative period. Results The goal of surgical correction was achieved in all cases. AOFAS score scale was used for assessment of functional status. The mean score increased from 57.0 to 93.6 points. Time and kinematic characteristics of walking improved 18 months after reconstruction. Discussion Due to pain, discomfort and cosmetic defects the patients seek medical care even if marked functional disorders are absent in brachymetatarsia. The analysis of walking in patients with unilateral brachymetatarsia shows difference between the sides, as well as a deviation from the age norm on the side of brachymetatarsia. As far as motor skills complete to be formed by 7 years of age and close-to-adults walking by 13 years, it seems appropriate to perform surgical correction of brachymetatarsia in this period. Сonclusion Lengthening of metatarsal bones improves weight-bearing of the foot, ensuring the correct walking skills and smoothness of gait. Restoration of the fourth metatarsal bone, along with elimination of metatarsalgia, improves the esthetic appearance and allows wearing normal shoes. The compressiondistraction method enables to solve the problem of elongation of short tubular bones in brachymetatarsia.